Penerapan Model Pembelajaran Contextual Teaching And Learning (Ctl) Dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Di Madrasah Bandar Lampung - Bahri, Saiful (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2017)
This study aims to determine the effect of the implementation of the inquiry type CTL learning model on critical thinking skills. The population in this study were eighth grade students of MTs. Al-Asy’ariyah Bandar Lampung Year 2015/2016. The research method used in this study is Quasi Experimental Design. The research design used in this quasi-experimental was the pretest-posttest control group design. The sampling technique is random sampling. The sample in this study consisted of two classes namely the experimental class and the control class. Data collection techniques in the form of tests to measure students' critical thinking skills and observations to observe behaviors that arise in students according to indicators of critical thinking skills. The results of hypothesis testing obtained thitung = 5.78, while ttabel at a significance level of 5% by 2.00, it can be said that thitung > ttabel. This shows that Ho is rejected and H1 is accepted, meaning that there is an influence of the inquiry type CTL learning model on students' critical thinking abilities.